2011
DOI: 10.3174/ajnr.a2801
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Assessment of the Epileptogenic Zone in Children with Localization-Related Epilepsy

Abstract: BACKGROUND AND PURPOSE:Patients with MR imaging-negative epilepsy could have subtle FCD. Our aim was to determine if structural changes could be identified by using DTI in children with intractable epilepsy, from MR imaging-visible FCD and MR imaging-negative localization-related epilepsy, that were concordant with the epileptogenic zone as defined by using the MEG dipole cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…[208][209][210] Localizing Seizure Focus and Propagation Diffusion abnormalities may be helpful in localizing or lateralizing epileptic focus. The localizing information provided by DTI has been shown to be concordant with other independent techniques, including structural MR imaging, EEG, equivalent current dipole, 211,212 Megnatoencephalography 213,214 and stereo-EEG. 215 Seizure onset areas show increased diffusivity in the cortical gray matter and white matter in the vicinity of the epileptic focus, whereas healthy cortex has decreased diffusivity in the inner and middle cortical fractions compared with healthy controls.…”
Section: Hs Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…[208][209][210] Localizing Seizure Focus and Propagation Diffusion abnormalities may be helpful in localizing or lateralizing epileptic focus. The localizing information provided by DTI has been shown to be concordant with other independent techniques, including structural MR imaging, EEG, equivalent current dipole, 211,212 Megnatoencephalography 213,214 and stereo-EEG. 215 Seizure onset areas show increased diffusivity in the cortical gray matter and white matter in the vicinity of the epileptic focus, whereas healthy cortex has decreased diffusivity in the inner and middle cortical fractions compared with healthy controls.…”
Section: Hs Resultsmentioning
confidence: 83%
“…215 Seizure onset areas show increased diffusivity in the cortical gray matter and white matter in the vicinity of the epileptic focus, whereas healthy cortex has decreased diffusivity in the inner and middle cortical fractions compared with healthy controls. 216 Focal cortical dysplasia (FCD) visible on conventional MR imaging 217 shows diffusion abnormalities concordant with the structural lesion, 213 and abnormal tracts may reflect ictal spread pathways, 218 although there is a lack of proof for this contention. At times, diffusion abnormalities around FCDs are more extensive, involving gray and deep white matter beyond MR imaging visible lesions, which can help to define the epileptogenic zone.…”
Section: Hs Resultsmentioning
confidence: 97%
“…Voxel-wise methods are also imperfect; for example, they can cause undesirable partial volume averaging effects via smoothing when using the statistical parametric mapping (SPM) approach for determining statistical significance. Additionally, entire WM measurements may not be taken into account when using the tract-based approach [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, DTI has also been beneficial in assisting in locating the epileptogenic zone. Widjaja et al 31 reported on the use of DTI to identify white matter changes in children who have negative results on MRI. The authors performed DTI image analysis "on a group of controls across individual patients" (26 age-matched healthy controls and 24 patients with epilepsy).…”
Section: Hemispherectomy: Historical Review and Recent Technical Advamentioning
confidence: 99%
“…Diffusion tensor imaging can help identify these subtle changes that might assist with lo calizing the affected hemisphere. 31 In addition, DTI can confirm completeness of hemispheric disconnection and identify persistent residual areas of connectivity that can hinder seizure outcome (Fig. 1).…”
Section: Hemispherectomy: Historical Review and Recent Technical Advamentioning
confidence: 99%